Nitric Oxide Synthase - Simple Enzyme-Complex Roles 2017
DOI: 10.5772/67267
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide Synthase in Normal Brain Function and Pathophysiology of Neural Diseases

Abstract: Nitric oxide synthase has three isoforms; according to their roles and tissues or cells they are involved. Neuronal NOS (nNOS) takes place in neuronal signalling, endothelial NOS (eNOS) takes place in vasodilation and inducible NOS (iNOS) takes place in immune responses. nNOS and eNOS are dominant but all isoforms have various roles in the central nervous system. nNOS and eNOS separately or together works in healthy brain during cognitive processes and in unhealthy brain during the pathology of related disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
0
5
0
3
Order By: Relevance
“…eNOS is an enzyme responsible for the generation of the majority of • NO in endothelial cells. This enzyme has several functions, namely the control of blood vessel tone, angiogenesis, and it is responsible for the majority of the • NO levels in the hippocampus and the cortex (Dagdeviren 2017). Despite a study nding higher levels of • NO in brain homogenates (Cardoso, Barros et al 2020), it does not seem to be due to higher eNOS content, but rather a possible increase in other isoforms of • NO synthase or a byproduct of redox reactions.…”
Section: Discussionmentioning
confidence: 99%
“…eNOS is an enzyme responsible for the generation of the majority of • NO in endothelial cells. This enzyme has several functions, namely the control of blood vessel tone, angiogenesis, and it is responsible for the majority of the • NO levels in the hippocampus and the cortex (Dagdeviren 2017). Despite a study nding higher levels of • NO in brain homogenates (Cardoso, Barros et al 2020), it does not seem to be due to higher eNOS content, but rather a possible increase in other isoforms of • NO synthase or a byproduct of redox reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Besides their central role in host defense against pathogens, nanomolar concentrations of SO/H 2 O 2 have neuroprotective functions, regulate neuronal proliferation and polarity, synaptic transmission, vesicle trafficking, and axonal transport, as well as regeneration and functional recovery after injury. 61,109,125,150,163 Nitric oxide is another radical present throughout the organism, produced by 3 different isoforms of NO synthase: the calciumdependent endothelial (eNOS) and neuronal (nNOS) isoforms, which are constitutively expressed, 30 and the calcium-independent inducible NOS (iNOS), expressed during inflammatory conditions and able to produce 700-fold to 1000-fold greater increase (mM-mM range) in NO compared with eNOS and nNOS. 27 In the nervous system, nanomolar concentrations of NO regulate blood-brain barrier integrity, neuronal development, differentiation, survival, 4,119,129 and synaptic transmission and plasticity.…”
Section: Nitroxidative Stressmentioning
confidence: 99%
“…Nitric oxide is another radical present throughout the organism, produced by 3 different isoforms of NO synthase: the calcium-dependent endothelial (eNOS) and neuronal (nNOS) isoforms, which are constitutively expressed, 30 and the calcium-independent inducible NOS (iNOS), expressed during inflammatory conditions and able to produce 700-fold to 1000-fold greater increase (µM–mM range) in NO compared with eNOS and nNOS. 27 In the nervous system, nanomolar concentrations of NO regulate blood–brain barrier integrity, neuronal development, differentiation, survival, 4,119,129 and synaptic transmission and plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive production of NO can lead to excitotoxicity, apoptosis, and inflammation. Van den Tweel E.R (2005) has shown that combined inhibition of neuronal nitric oxide synthase (nNOS) and inducible NOS (iNOS) can reduce hypoxia-ischemia-induced brain damage in 12-day-old rats [29]. However, inhibition of eNOS is harmful, as it leads to a decrease of cerebral blood flow and to increase of hypoxic effects.…”
Section: Fig 1 Relative Normalized Expression Of Mrna Of (A) Nnos mentioning
confidence: 99%